Analisis Riwayat Israiliyat tentang Kisah Nabi Daud dalam Tafsir Ath-Thabari dan Tafsir Abdurrazzaq Ash-Shan’ani: Studi QS. Shad 38: 21-25) - Aminullah, Muhammad; Irsyadi, Najib (Tasamuh: Jurnal Studi Islam, 2025)
this study analyzes the Israiliyat narrations about Prophet David in QS. Shad (38:21-25), which recounts his encounter with two disputing individuals. It focuses on how Ibn Jarir al-Thabari and Abdurrazzaq al-Shan'ani use Israiliyat in their interpretations and examines the sources and validity of these narrations. this study Using a descriptive qualitative method with a literature study approach, this research relies on Tafsir al-Thabari, Tafsir Abdurrazzaq al-Shan'ani, and other relevant sources. The findings reveal differences in the sanad and interpretative structures, yet both Tafsir works share a common initial source from al-Hasan. The narration describes the verse as both a test for Prophet David and a reprimand, mentioning that he intended to marry the wife of his subordinate. To evaluate the authenticity of these narrations, this study refers to the perspectives of classical and contemporary Tafsir scholars.